An Enterprise Approach to the Next Generation Systems Environment for the Australian Hydrographic Service (AHS) - Halls (Australia), Ian W. (The International Hydrographic Review, 2015)
The Australian Hydrographic Service (AHS) of the Royal Australian Navy (RAN) has been at the forefront of digital hydrographic information management and production for many years. In the early 2000s, the AHS had a Digital Hydrographic Data Base (DHDB) developed and implemented to enable the efficient and effective management of hydrographic data, the generation of multiple hydrographic products and distribution capabilities for these products. The DHDB suffered from a number of technical shortcomings and whilst implemented, was not maintained as a contemporary capability for several years. In 2011, with the DHDB finally accepted, evolutionary sustainment commenced to re-invigorate the DHDB capability to be a contemporary solution. This article provides an overview of this evolutionary sustainment initiative.